FINANCIAL INCLUSION DAN STABILITAS KEUANGAN DI INDONESIA - Baginda Parsaulian (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2022)
The financial sector has an important role in the economy of a country in the current era of globalization. Financial Technology (Fintech) has changed the financial system to be easier and faster where in the transaction process no longer uses physical money (currency) and demand deposits (demand deposits) or bank accounts, but a number of funds that have been transferred and recognized as balances in the application certain and can be used to carry out financial transactions the same as using physical money (currency) but it is easier and more practical to use a cellular phone and the application. Financial inclusion implemented by the government focuses on increasing financial access for people who have not yet enjoyed the services of formal financial institutions due to barriers to accessing them. Financial inclusion in practice can have both positive and negative impacts. As a positive impact, financial inclusion besides being able to overcome income inequality also has the potential to improve financial stability, this is because the poor's access to savings from formal financial institutions can increase the capacity of households to manage financial vulnerabilities caused by the adverse effects of the crisis, diversify the funding base from institutions. that can reduce shocks during global crises, increase economic resilience by accelerating growth, facilitating diversification, and reducing poverty. The negative impact of financial inclusion is caused by a decrease in credit standards due to financial institutions trying to reach the lower class of the unbankable in the form of a decrease in loan requirements, this can increase the risk of a bank's reputation due to improving financial services facilities in several countries which lower the standard for establishing a financial institution for the region. rural areas, and can cause instability due to immature and sufficient regulation from microfinance institutions.